2020
DOI: 10.1016/j.ecolind.2020.106128
|View full text |Cite
|
Sign up to set email alerts
|

Responses of reef bioindicators to recent temperature anomalies in distinct areas of the North Ari and Rasdhoo atolls (Maldives)

Abstract: Assessments of reef sediments in the North Ari Atoll (Maldives) were conducted in 2015 and 2018 on reefs of three islands with different management strategies: community, resort, and uninhabited. Indices applied were the Foraminifera in Reef Assessment and Monitoring Index (FI) and the Sediment Constituents Index (SI). Both indices are based on shells or fragments of functional groups, which for the FI are foraminiferal shells and for the SI are sediment components. The FI is considered to be an indicator of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
1
3
0
3
Order By: Relevance
“…While this indicates the ecosystem as a whole is still in a stressed state, following the 2015 and 2016 bleaching events, the higher abundance of juveniles in 2018 indicates that the Amphistegina populations are resilient. This conclusion is consistent with the Maldivian coral and benthic foraminiferal assemblage studies by Caragnano et al (submitted) and Beccari et al (2020), conducted on the same reefs and sites. They found that, while high proportions of the reef cover were dominated by sediment and coral rubble (dead coral skeletons), small (<5 cm) coral colonies were abundant, supporting a natural resilience and possible recovery for these reefs back to their pre (2015 and 2016) bleaching state.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…While this indicates the ecosystem as a whole is still in a stressed state, following the 2015 and 2016 bleaching events, the higher abundance of juveniles in 2018 indicates that the Amphistegina populations are resilient. This conclusion is consistent with the Maldivian coral and benthic foraminiferal assemblage studies by Caragnano et al (submitted) and Beccari et al (2020), conducted on the same reefs and sites. They found that, while high proportions of the reef cover were dominated by sediment and coral rubble (dead coral skeletons), small (<5 cm) coral colonies were abundant, supporting a natural resilience and possible recovery for these reefs back to their pre (2015 and 2016) bleaching state.…”
Section: Discussionsupporting
confidence: 92%
“…1). All three were previously sampled in 2015 during the International Union for Conservation of Nature (IUCN) REGENERATE Cruise and thus the 2018 sampling campaign served as the next step in establishing a time-series to monitor the recovery and resilience status of these reefs following a mass-bleaching event (Pisapia et al, 2017a;Beccari et al, 2020;Caragnano et al, submitted). Whilst the REGENERATE cruise aimed to establish if different island management strategies impacted the health of the reef, this was not the primary focus of the 2018 sampling campaign.…”
Section: Study Sitementioning
confidence: 99%
“…This in‐depth understanding of SAM dynamics is pivotal for predicting the impact of anthropogenic warming on the extensive tropical ecosystems of the Maldives, especially given the SAMs dominant influence on the regional physicochemical properties. Coral reef ecosystems are susceptible to environmental perturbations, with many organisms presently living close to or at their ecological as well as thermal limits (Beccari et al., 2020; NOAA Coral Reef Watch, 2015; Stainbank, Spezzaferri, Beccari, et al., 2020). With the future prospect of increased warming trends, using recognized past analogs to better understand the current “Anthropocene era” will aid in the prediction and understanding of how these ecosystems may be affected at the end of this century.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, thermal stress is a primary threat to these ecosystems as both organisms have similar bleaching thresholds (30.9°C-31.0°C: NOAA Coral Reef Watch, 2018; Schmidt et al, 2011), which is regularly exceeded during El Niño events (NOAA Coral Reef Watch, 2018). This thermal stress was particularly evident during the three recent mass bleaching events (1998, 2010, and 2016) which led to extensive mortality, protracted recovery times, and an overall degradation of the Maldivian reef environments (Beccari et al, 2020;Pisapia et al, 2019;Stainbank, Spezzaferri, Beccari, et al, 2020). The ability for corals and Amphistegina to recover, following a bleaching event, is dependent on the duration, frequency, and severity of these periods with elevated SSTs (Pisapia et al, 2016(Pisapia et al, , 2019.…”
Section: Future Implications For the Maldives Tropical Ecosystems And Inner Sea Physicochemical Propertiesmentioning
confidence: 99%
“…En efecto, muchas especies de foraminíferos responden ante cambios ambientales de manera similar a como lo hacen los corales escleractínios. Por ejemplo, las conchillas de muchas especies se componen de carbonato de calcio, y algunas especies se consideran constructoras arrecifales y presentan simbiosis con zooxantelas, por lo que sus requerimientos ambientales también son similares (Hallock et al, 2003;Beccari et al, 2020;O'Brien et al, 2021). De tal forma, estos organismos han sido considerados como indicadores biológicos (ambientales y paleoambientales) ideales ya que su ciclo de vida corto (p.…”
Section: Intropica Introducciónunclassified